Characteristics Nanoparticle of Propolis Ethanol Extracts with Variations of Chitosan-Sodium Alginat (Indian Journal of Forensic Medicine & Toxicology, 2020)
Nanoencapsulation technology has many advantages, which include important roles in drug delivery andprotection of bioactive components that have perishable stability, one of which is polyphenol compounds.Propolis which contains high levels of polyphenol compounds has been used as an antioxidant for variousdiseases. By making nanoparticles from propolis, it can maintain the stability of polyphenol compoundsfrom propolis and increase the effect of treatment through optimal delivery. Nanoformulations containingethanol extract of propolis were absorbed by chitosan-sodium alginate using an ionotropic pre-gelationmethod. Optimization is carried out at various concentrations of chitosan, namely 0.05%; 0.075%; 0.1% and0.125% , with the use of the same sodium alginate concentration which is 0.0063%. Testing of nanoparticlecharacteristics includes particle size and morphology and adsorption efficiency (EE) consisting of totalflavonoid and total polyphenol values. The increase in chitosan polymer is directly proportional to theincrease in particle size, but does not occur in the absorption efficiency value. The 0.05% chitosan formulashowed the absorption of polyphenol compounds at 99.41% with particle sizes of 259.12 nm